Roselle (Hibiscus sabdiriffa) Polyphenol-Rich Extract Prevents Testicular Damage of Diabetic Rats - Siti Balkis Budin, Wan Zafirah Abdul Rahman, Fatin Farhana Jubaidi, Nur Liyana Mohammed Yusof, Izatus Shima Taib, Satirah Zainalabidin (Journal of Applied Pharmaceutical Science, 2018)
Oxidative stress plays a critical role in diabetes-induced complications including injurious effect on male reproductive organ. Hibiscus sabdariffa Linn. or roselle possesses antioxidant properties and widely used to treat various diseases. The study was aimed to evaluate the effect of H. sabdariffa polyphenol-rich extract (HPE) from the calyces towards male reproductive organs in diabetic rats. Twenty-four male rats were divided into three groups; (i) normal non-diabetic (NDM), (ii) diabetic (DM) and (iii) diabetic treated with HPE (DM + HPE) groups. Diabetes was induced with streptozotocin (60 mg/kg, single i.p.). HPE (100 mg/kg) was administrated by forced feeding for 28 consecutive days before being sacrificed to harvest their reproductive organs. Results showed that superoxide dismutase (SOD) and catalase (CAT) activities as well as gluthathione (GSH) levels in the testis homogenate of DM + HPE group were significantly higher (p < 0.05) compared to DM group. Meanwhile, significantly lower levels of malondialdehyde (MDA) and protein carbonyl (PC) were observed in DM + HPE group compared to DM group. The histological observation showed morphological alteration of the testis in DM group, which was impeded following supplementation of HPE. In conclusion, this suggests that HPE supplementation is able to prevent oxidant injury of testis of diabetic rats.
Keywords: Diabetes mellitus Type 1,roselle, male reproductiveorgans, oxidative stress.